CRYOINJURY TO MAMMALIAN SPERMATOZOA: AN OVERVIEW - Naikoo, Mehrajuddin; Patel, D M; Lekshmi , P; Vala , K B (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Despite many advantages of semen cryopreservation, there is an apparent contradiction between the concept of preservation and experimental findings that spermatozoa can be damaged by the preservation process itself. Sperm cryoinjury is caused by each step or a combination of the steps of cryopreservation. In this paper, various mechanisms of mammalian sperm cryoinjury (e.g., cryoprotective agents and osmotic injuries, hypothermic injury, cryoinjury during storage period, cryoinjury associated with the warming process etc) are briefly reviewed. In the light of this review, further understanding of fundamental cryobiology is needed to develop optimal cryopreservation conditions for sperm of individual species.